Improvement the RPL Performance in Wireless Sensor Networks with Mobile Sink Nodes - خليفة جمال; قاسم صفوان (Latakia University Journal -Engineering Sciences Series, 2020)
RPL (Routing Protocol for low power and lossy network) was designed, to work in networks that contain a large number of smart devices, and able to communicate with users over the Internet. This protocol is based on the distance Victor algorithm and forms evidence of network components similar to trees that do not contain any loops. This structure is called DODAG (Destination Oriented Acyclic Graphs). In this research we will work on a wireless sensor network with a mobile sink node .This network uses the RPL protocol, we will modify this protocol to make the sink node move to a specific node based node’s weight, which depends on the number of neighbors of this node, the number of hops from this node to the sink node, the remaining energy in this node, and the number of packets generated in this node. We will simulate the modifying RPL and the results will be compared with the results of previous studies that have modified the protocol according to different parameters.